Statistical Fluctuations of Energy Spectra in the Isobar A = 68 Nuclei - Hamoudi, Adel. K.; Abd Alabas, Hayder A. (Iraqi Journal of Science, 2021)
Statistical fluctuations of nuclear energy spectra for the isobar A = 68 were examined by means of the random matrix theory together with the nuclear shell model. The isobar A = 68 nuclei are suggested to consist of an inert core of 56Ni with 12 nucleons in f5p-space (2p3/2, 1f5/2 and 2p1/2 orbitals). The nuclear excitation energies, required by this work, were obtained through performing f5p-shell model calculations using the isospin formalism f5pvh interaction with realistic single particle energies. All calculations of the present study were conducted using the OXBASH code. The calculated level densities were found to have a Gaussian shape. The distributions of level spacing P(s) and statistic for the considered classes of states, obtained with full Hamiltonian of f5pvh (absence of the off-diagonal Hamiltonian) calculations, showed a chaotic (regular) behavior and coincided well with the distribution of Gaussian orthogonal ensemble (Poisson). Moreover, these distributions were independent of spin (J) and isospin (T)